DNA database of populations from different parts in the Kingdom of Thailand - Jittima Shotivaranon (2018)
The polymorphism of 15 short tandem repeat (STR) loci-D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D2S1338, D19S433, vWA, TPOX, D18S51, D5S818 and FGA from AmpFlSTR®Identifiler®PCR amplification kit were analysed in 929 unrelated individuals living in the north, northeast, central and south of Thailand. The comparison between these four subpopulations demonstrated that subpopulations in the north and northeast were different in two loci from all paired groups while those in the north, central and south were closely related. The inter-population comparisons between combined Thai population and other ethnic groups including Eastern Chinese, Japanese, Iraq and Egyptian revealed that Eastern Chinese and Thai were closely related. © 2009 Elsevier Ireland Ltd. All rights reserved.